Analysis of the Stayability in Milk Buffaloes using Survival Models - Galeazzi, P. M. [UNESP]; Silva, J. A. I. I. de V.; Sesana, R. C. [UNESP]; Seno, L. O. [UNESP]; Borquis, R. R. A. [UNESP]; Lima, A. L. F. [UNESP]; Tonhati, Humberto [UNESP] (Pagepress Publ, 2007)
In this study the trait Stayability (SA) was evaluated according to the year of cull after first calvin, i.e., SA 1 to 6 for 1 to 6 years from first calving in lactating females from bubaline milk herds spread in nine farms located in São Paulo state. Informations were used regarding 1027 lactating Murrah breed buffaloes. The statistical analyses were made using LIFEREG (SAS, 1999) procedure. The SA was evaluated using the fixed effects: farm production, birth year, calving season (Season 1- April to September and Season 2 October - March) and class of milk yield at 270 days. The age at first calving (AFC) was considered as a random effect. The mean observed for total milk yield was 1458.75Kg. Calving Season 2 encloses 65.6% of births. The means of cull age, in months, and the percentage of SA were, respectively: 10.69 e 69% (SA1), 19.30 e 63% (SA2), 26.4 e 54% (SA3), 33.15 e 42% (SA4), 38.53 e 36% (SA5) e 42.65 e 26% (SA6). It is verified that most of culls happens after the first lactation, among the sixth and eleventh month after first calving. It was observed that the factors: farm production, birth year and class of milk yield at 270 days affected significantly all SAs. Factors like calving season and the age at first calving (AFC) were only significant for SAL Being significant the factor AFC in level of 1% and factor time in 10%. For other SAs these factors were not statistically significant.
Keywords: Bubabus bubalis; Cull Age; Milk yield